Obraz Kirgistanu w dzienniku podróży Dach Świata jeszcze raz .......... 359 - Pasterska, Jolanta (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
KYRGYZSTAN IN THE JOURNEY DIARY DACH ŚWIATA JESZCZE RAZThe paper discusses Anna Frajlich’s travel diary based on her visit to Kyrgyzstan in 2014.This is the place where she was born in 1942. The diary was published in the literary magazine eleWator in 2015. The author focuses her discussion on three issues: the traveler, the purpose of the trip and the manner in which the place is described. A trip to Kyrgyzstan has become an opportunity for the poet to think on her identity and place in the world. In this perspective, Anna Frajlich’s journey to the “Roof of the World” is a personal and universal experience.